The Relationship of Daily Spiritual Experience with Self-Care among the Elderly in Gonbad-e-Kavos City, Iran, in 2017 - Golbahar Akhoundzadeh; Faezeh Pagheh; Razieh Safaei (Vesnu Publications, 2020)
Introduction: With the aging, changes will occur in the health dimensions of elderly. Due to these changes, the elderly is prone to damage and decreased quality of life. As a result, health promotion behaviors become more important. Religion and spirituality can have a positive impact on mental and physical health. As age grows, religious beliefs and spiritual health also increase. Similarly, the adherence to religious beliefs and instructions increases the motivation of the individual to create and strengthen self-care behaviors. This study aimed to investigate the relationship between daily spiritual experiences and self-care among the elderly. Materials and Methods: This descriptive correlational study was conducted on 200 elderly people in Gonbad-e-Kavos City, Iran, in year 2017, using non-random sampling method. The data gathering tool was a questionnaire of daily spiritual experiences and a self-care questionnaire for the elderly. The data were analyzed using Pearson correlation coefficient, ANOVA, and independent t tests. Results: The mean scores of spiritual experiences and self-care among the elderly were 81.31 ± 9.63 and 51.97 ± 5.22, respectively. There was not any significant relationship between the two variables based on the Pearson correlation coefficient (P = 0.91). There was a significant difference between the daily spiritual experiences and job (P = 0.007), as well as between the self-care and marital status (P = 0.020). Conclusion: The level of spiritual well-being was high among the elderly; and considering their religious culture and beliefs, we can help them to improve their quality of life by identifying and strengthening their spiritual needs.